The effect of NCO-polyol on the properties of low-density polyethylene/water hyacinth fiber (Eichhornia crassiper) composites - Supri, A. Ghani, Dr.; Ismail, H. (Taylor & Francis Group, LLC., 2010)
Link to publisher's homepage at http://www.taylorandfrancisgroup.com/